Tailoring Governance System Design Through Capability Level Identification Using COBIT 2019 at a Paper and Mills Company - Abraham Lelengboto; Gabriell Mandoya; Joe Yuan Mambu (STMIK Budi Darma, 2022)
IT investments and services run the risk of failing without IT governance. How well IT governance is implemented will determine how effective organizational governance is. As a result, it is crucial for businesses to carry out an IT governance audit to determine what issues are most important. One of the nation's top paper manufacturer, PT. Indah Kiat Pulp and Paper, a subsidiary of Asia Pulp and Paper Sinarmas, has never been go through COBIT 2019 audit. In order to support their aforementioned vision, we identify their IT governance priorities using the COBIT 2019 framework which will aid them in focusing their efforts that will help them attaining their objectives and goals. We applied the COBIT 2019’s Design Factor 1 through 10 and concluded several points: they focuses on competitive portfolio and also have risk in internal business process, compliances and innovations. They also regards IT as crucial for daily operation and also the driver for innovation while also utilize agile and devops for their IT implementation. Lastly, the COBIT 2019 Toolkit suggested capability of four: EDM01, APO12, BAI02, BAI03, BAI06, BAI07, DSS011, DSS04, DSS05, MEA03 and MEA04. These 11 core models would be the base for the governance system design